2018
DOI: 10.13181/mji.v27i3.1618
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain polyunsaturated fatty acid status in first-trimester pregnant women

Abstract: Background: The beneficial effects of long-chain polyunsaturated fatty acid (LCPUFA) on maternal health have been widely investigated in pregnant women. First-trimester supplementation of LCPUFA has been reported to play a role in the inflammatory response, thus reducing a preterm birth and preeclampsia. However, there is a lack of studies investigating the blood concentration of LCPUFA in pregnant women in Indonesia. This study was conducted to evaluate the status of LCPUFA in first-trimester pregnant women i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Our study showed most of first trimester pregnant women has low level of iron, zinc, and vitamin D 12 . Also, a study about LCPUFA status in first trimester of pregnancy showed that most of pregnant women in Indonesia had low intake and blood concentrations of LCPUFA, including LA, AA, ALA, EPA, and DHA 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed most of first trimester pregnant women has low level of iron, zinc, and vitamin D 12 . Also, a study about LCPUFA status in first trimester of pregnancy showed that most of pregnant women in Indonesia had low intake and blood concentrations of LCPUFA, including LA, AA, ALA, EPA, and DHA 13 .…”
Section: Introductionmentioning
confidence: 99%